2001
DOI: 10.1016/s0020-7292(01)00427-1
|View full text |Cite
|
Sign up to set email alerts
|

Holding up a mirror: changing obstetric practice through criterion‐based clinical audit in developing countries

Abstract: The objective of the study described is to assess the feasibility and effectiveness of using a criterion-based clinical audit to measure and improve the quality of obstetric care at the district hospital level in developing countries. The focus is on the management of five life-threatening obstetric complications--hemorrhage, eclampsia, genital tract infection, obstructed labor and uterine rupture was audited using a "before and after" design. The five steps of the audit cycle were followed: establish criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 2 publications
3
106
1
2
Order By: Relevance
“…12,14 The study demonstrated the feasibility of collecting data from various types of health facilities. Data could be extracted from 10-12 records in an eight-hour working day.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…12,14 The study demonstrated the feasibility of collecting data from various types of health facilities. Data could be extracted from 10-12 records in an eight-hour working day.…”
Section: Discussionmentioning
confidence: 94%
“…Three days were spent at each of the smaller health facilities with a delivery rate of less than 10 per month, 16 days at the busiest hospital (50 deliveries per month). A nurse-midwife was recruited for data collection, although others have successfully used non-medical personnel 12 with advantages of greater objectivity of the data collector and less disruption to clinical service provision. Other assessments of maternity care used several instruments, including structured observations, record review, inventories, patient flow studies and interviews, [15][16][17][18][19] rather than a single case extraction form and are likely to require even more time and resource inputs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also several studies of facilitypbased audits of perinatal deaths, 20 uterine rupp p ture, 21 nearpmisses [22][23][24] or criterionpbased audit. 25,26 However, controlled evaluation studies of audit interventions are rare and the absolute or relative effects of these approaches on professional practices and outcomes are generally only small to moderate.…”
Section: Special Theme -Estimating Mortalitymentioning
confidence: 99%